UJI BERBAGAI UKURAN BULBIL DAN DOSIS DOLOMIT TERHADAP PERTUMBUHAN PORANG (Amorphophallus muelleri Blume.) PADA MEDIA GAMBUT - Yudira, Muhammad; Hamzah, Anthony; Khoiri, M. Amrul (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
Porang (Amorphophallus muelleri Blume.) is one of the plants that has the potential to be cultivated on peatlands. The limited number of seeds and fertile land that is decreasing indicates that efforts need to be made to increased the production and productivity of porang. This research aimed to increase the growth of porang on peat media for 6 months after planting by using bulbil size with dolomite. This research was conducted in the Technical Management Unit of Experimental Gardens, Faculty of Agriculture, Riau University from October 2020 to April 2021. This study was 4x3 factorial experiment arranged according to completely randomized design. The first factor was bulbil size which consists of four levels, (at 5,0 g-7,5 g; >7,5 g-10 g; >10 g-12,5 g; >12,5 g-15.0 g) and the second factor dose of dolomite consists of three levels, (at 2,5 ton.ha-1; 5,0 ton.ha-1; 7,5 ton.ha-1). Parameters observed were growth power, plant height, stem diameter, canopy width, rachis length, number of leaves, number of leaflets, and number of bulbil formed. Based on the results of the study, it was shown that porang has the potential to be developed in Riau Province, because it is able to adapted well to peat soils. The use of bulbil size 12,5-15,0 g and dolomite at a dose of 7,5 ton.ha-1 showed a better response to the growth of porang plants than other treatments. The results showed that the application of dolomite can improve some of the chemical properties of peat soil. Keywords : Bulbil, Dolomite, Porang, Peat